1989
DOI: 10.1116/1.584528
|View full text |Cite
|
Sign up to set email alerts
|

Charging effects from electron beam lithography

Abstract: This paper discusses initial results from a study of pattern placement errors due to substrate charging in fixed spot direct write electron beam systems. Experimental results obtained from small crosses written with 20 keY electrons near large pads indicate charging~induced errors of 0.2 flm can occur over 1 mm away from the pad. We present a simple theory that describes the placement errors for large cross-pad separations. The theory suggests that the substrate-electron interaction is strong and long range. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 0 publications
0
23
1
1
Order By: Relevance
“…This effect is caused by the artifact of the electron beam lithography process employed in the fabrication: when two elements are closer to each other, their actual individual sizes under the same resist exposure conditions become larger due to local charging effects. [ 26 ] Thus, as k 11 increases, the actual sizes for L 1 and L 2 increase, redshifting the branches. The good agreement between measured and simulated refl ectance spectrum color maps validates our physical picture of the high-effi ciency photon-SPP conversion process.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 92%
“…This effect is caused by the artifact of the electron beam lithography process employed in the fabrication: when two elements are closer to each other, their actual individual sizes under the same resist exposure conditions become larger due to local charging effects. [ 26 ] Thus, as k 11 increases, the actual sizes for L 1 and L 2 increase, redshifting the branches. The good agreement between measured and simulated refl ectance spectrum color maps validates our physical picture of the high-effi ciency photon-SPP conversion process.…”
Section: Full Paper Full Paper Full Papermentioning
confidence: 92%
“…This observation is similar to that of high energy electron beam lithography. 13 No significant line deflection or pattern distortion was observed on patterns exposed on a silicon substrate coated with a 200 nm thick SiO 2 film. Patterns exposed on a silicon substrate having 480 nm thick SiO 2 layer showed significant line deflection 2 kV.…”
Section: Line Deflection Measurementsmentioning
confidence: 96%
“…Currently, LESiS does not model hole recombination, so positive charges can only be eliminated when a negative charge is tabulated in the same bin, and vice versa. Laboratory experiments have found that charge build-up can be measured in a resist long after exposure, 9,10 so it is assumed that lifetime of electrons or holes is significantly longer than the exposure time. This data can be fed back into the simulation to model time dependent effects.…”
Section: Methodsmentioning
confidence: 99%
“…10 This experiment, in which 1700 EUV photons were run -simulating a dose of 27.2 mJ/cm 2 , modeled the effect of charging in EUV exposures. A 10x10 nm EUV photon source exposed a 60 nm resist film on top of a silicon substrate; 10 nm of vacuum separated the resists and the source.…”
Section: Coulombic Force Modelingmentioning
confidence: 99%